Solution‐Processed GaSe Nanoflake‐Based Films for Photoelectrochemical Water Splitting and Photoelectrochemical‐Type Photodetectors. (21st January 2020) - Zappia, Marilena Isabella; Bianca, Gabriele; Bellani, Sebastiano; Serri, Michele; Najafi, Leyla; Oropesa‐Nuñez, Reinier; Martín‐García, Beatriz; Bouša, Daniel; Sedmidubský, David; Pellegrini, Vittorio; Sofer, Zdeněk; Cupolillo, Anna; et al.
Abstract: Gallium selenide (GaSe) is a layered compound, which has been exploited in nonlinear optical applications and photodetectors due to its anisotropic structure and pseudodirect optical gap. Theoretical studies predict that its 2D form is a potential photocatalyst for water splitting reactions. Herein, the photoelectrochemical (PEC) characterization of GaSe nanoflakes (single‐/few‐layer flakes), produced via liquid phase exfoliation, for hydrogen evolution reaction (HER) and oxygen evolution reaction (OER) in both acidic and alkaline media is reported. In 0.5 m H2 SO4, the GaSe photoelectrodes display the best PEC performance, corresponding to a ratiometric power‐saved metric for HER (Φsaved, HER ) of 0.09% and a ratiometric power‐saved metric for OER (Φsaved, OER ) of 0.25%. When used as PEC‐type photodetectors, GaSe photoelectrodes show a responsivity of ≈0.16 A W −1 upon 455 nm illumination at a light intensity of 63.5 µW cm −2 and applied potential of −0.3 V versus reversible hydrogen electrode (RHE). Stability tests of GaSe photodetectors demonstrated a durable operation over tens of cathodic linear sweep voltammetry scans in 0.5 m H2 SO4 for HER. In contrast, degradation of photoelectrodes occurred in both alkaline and anodic operation due to the highly oxidizing environment and O2 ‐induced (photo)oxidation effects. The results provide new insight into the PEC properties of GaSe nanoflakes for their exploitation in photoelectrocatalysis, PEC‐type photodetectors, and (bio)sensors. Abstract : Two‐dimensional group‐III monochalcogenides, namely, gallium selenide (GaSe) nanoflakes, are produced and processed by scalable methods (liquid‐phase exfoliation and spray coating film deposition) to be directly exploited for photoelectrochemical water splitting and photoelectrochemical‐type photodetectors.